Strategi Human Resources Development Department Dalam Meningkatkan Kualitas Karyawan Pada Hotel Meruorah Komodo Labuan Bajo - Arnoldus Jeharu; Agus Wahyudi; Yohanes Paulus Hanny Wadhi (JURNAL AKADEMISI VOKASI, 2025)
The purpose of this research to analyze the strategies implemented by the Human Resources Development (HRD) department to improve the quality of employees at the Meruorah Komodo Labuan Bajo Hotel. The research method used is qualitative with a case study approach, involving in-depth interviews, participatory observation, and document analysis at the Meruorah Komodo Labuan Bajo Hotel. The results show that the HRD at Meruorah Hotel has implemented several key strategies that significantly contribute to improving employee quality. First, training and development. Second, the Internal Development Program (IDP) or mentoring and coaching. Third, career development. Fourth, consistent recognition and rewards increase employee motivation and loyalty or retention. Fifth, a focus on employee well-being has been proven to increase job satisfaction and productivity. The implementation of comprehensive and integrated HRD strategies is key to improving the quality of employees at the Meruorah Komodo Labuan Bajo Hotel.